Effective Leadership Strategies in Facing the Digital Transformation Era (Case Study PT XYZ) - Putri, Nabila Salsabila (Formosa Journal of Sustainable Research, 2024)
In the current era of digital transformation, companies are urged to use digital technology to survive and compete in the industrial market. Therefore, companies must synergize with employees to master digital technology. The right strategy selection and adequate human resource management are among the key factors for successful change. This is where leaders play a crucial role in motivating employees. The purpose of this research is to identify effective leadership strategies to influence employee motivation to adopt new technology. The research method used is a qualitative approach. In this study, data validity is tested using triangulation techniques, and data is collected through interviews with company leaders directly as informants and two employees of different ages and genders. The results of this analysis indicate that effective leadership strategies can indeed motivate employees towards change, including digital transformation. This has been implemented by PT XYZ, located in the Rasuna Said area. Research conducted by PT XYZ shows that a leader can motivate employees to adopt new technology in line with the era of digital transformation. The analysis also reveals that the results of this research align with the theory proposed by Douglas McGregor, specifically Theory Y